Estudos microrreológicos da blenda PBT/SAN - Ito, Edson Noriyuki (2006)
This work was motivated by the need of a better understanding of the microrheological characteristics of polybutylene terephthalate, PBT, polymer blends, such as the matrix phase PBT and the styrene-acrylonitrile, SAN copolymer as dispersed phase. The main purpose of the microrheological studies carried out was to analyze the rheological behavior and the morphology, as well as their correlation, in the preparation of the PBT/SAN immiscible blend, with and without the use of an interfacial compatibilizer. The rheological behavior was analyzed by torque rheometry, rotational rheometry with parallelplates geometry, and capillary rheometry. The interfacial tensions were measured by the modified ellipsoidal drop retraction method, using an optical polarized light microscope coupled to a hot stage. Two complementary techniques were used in the morphological analyses: scanning electron microscopy (SEM) with tetrahydrofuran (THF) extraction of the dispersed phase, and transmission electron microscopy (TEM) with rutene tetroxide (RuO4) deposition in the dispersed phase. The interfacial tension between the PBT polymer and the SAN copolymer was found to increase as the molar mass of the PBT increased. The use of rotational rheometry with parallel plates at low shear rates allowed the increase in viscosity to be quantified as a function of the reaction of the polymeric macromolecules in the PBT/SAN blend compatibilized or not with the interfacial compatibilizer, the MMA-GMA-EA copolymer. Based on the morphological characterizations, an analysis was made of the fibril formation mechanisms, break up and coalescence of the particles of dispersed phase and their interactions with the addition of interfacial compatibilizers. The rotational rheometry at low shear rates proved to be extremely efficient in the analysis of blend compatibilization, which is usually analyzed by torque rheometry. It was checked that, at high shear rates, the viscosity ratio influenced the formation of more finely dispersed phases.